Vascular permeability in a human tumour xenograft: molecular charge dependence - Dellian, M (Nature Publishing Group, 2000)
Molecular charge is one of the main determinants of transvascular transport. There are, however, no data available on the effect of molecular charge on microvascular permeability of macromolecules in solid tumours. To this end, we measured tumour microvascular permeability to different proteins having similar size but different charge. Measurements were performed in the human colon adenocarcinoma LS174T transplanted in transparent dorsal skinfold chambers in severe combined immunodeficient (SCID) mice. Bovine serum albumin (BSA) and IgG were fluorescently labelled and were either cationized by conjugation with hexamethylenediamine or anionized by succinylation. The molecules were injected i.v. and the fluorescence in tumour tissue was quantified by intravital fluorescence microscopy. The fluorescence intensity and pharmacokinetic data were used to calculate the microvascular permeability. We found that tumour vascular permeability of cationized BSA (pI-range: 8.6–9.1) and IgG (pI: 8.6–9.3) was more than two-fold higher (4.25 and 4.65 × 10(−7)cm s(−1)) than that of the anionized BSA (pI ≈ 2.0) and IgG (pI: 3.0–3.9; 1.11 and 1.93 × 10(−7)cm s(−1), respectively). Our results indicate that positively charged molecules extravasate faster in solid tumours compared to the similar-sized compounds with neutral or negative charges. However, the plasma clearance of cationic molecules was ∼2 × faster than that of anionic ones, indicating that the modification of proteins enhances drug delivery to normal organs as well. Therefore, caution should be exercised when such a strategy is used to improve drug and gene delivery to solid tumours. © 2000 Cancer Research Campaign